Electronically current mode all-pass filter with only one grounded capacitor - Tongkulboriboon, Seangrawee; Pawarangkoon, Prajuab; Petchakit, Wijittra; Kiranon, Wiwat (My University, 2005)
A novel current mode first order all-pass filter with electronically tunable feature based on second generation current controlled conveyor (CCCII) is presented. The configuration of the proposed circuit is simple and very attractive for monolithic circuits owing to using only one grounded capacitor and two CCCIIs. Phase shift characteristic of the current mode all-pass filter can be controlled by dc bias currents of the CCCIIs. The proposed circuit is verified by SPICE simulation and applied in current mode quadrature oscillator realization. The results from simulations are included in order to confirm the validity of the proposed circuits.